2013
DOI: 10.1007/s00106-012-2592-0
|View full text |Cite
|
Sign up to set email alerts
|

Der Video-Kopfimpulstest

Abstract: By means of the vHIT it is possible to obtain a side-specific and quantitative assessment of hVOR. Video-head impulse test is a reliable tool for vestibular testing even in bedside examinations of patients suffering from dizziness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 18 publications
0
5
0
6
Order By: Relevance
“…Covert catch-up saccades could be demonstrated in 13.7% whereas in 86.3% overt catch-up saccades alone or in combination with covert catch-up saccades were found. The authors concluded that the vHIT is superior to the clinical HIT because in approximately one in eight cases with acute or chronic peripheral vestibular syndrome a covert catch-up saccade can be detected, which would otherwise have been undetectable by the clinical HIT [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Covert catch-up saccades could be demonstrated in 13.7% whereas in 86.3% overt catch-up saccades alone or in combination with covert catch-up saccades were found. The authors concluded that the vHIT is superior to the clinical HIT because in approximately one in eight cases with acute or chronic peripheral vestibular syndrome a covert catch-up saccade can be detected, which would otherwise have been undetectable by the clinical HIT [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28]. In anderen Studien wurden ebenfalls normale Gain-Werte bei peripher-vestibulären Störungen gefunden [9,11,29,30]. Als Erklärung wurden u. a. Vorgänge in der Erholungsphase peripherer Vestibulopathien diskutiert [11,30,31].…”
Section: Vorkommen Von Pathologischen V-kit-parameternunclassified
“…Die Gain-Asymmetrie beim V-KIT wurde bereits in zahlreichen Studien als Äquivalent zum CP-Wert der kalorischen Prüfung diskutiert, da bei der GA wie beim CP-Wert das Testergebnis ipsilateral mit kontralateral verglichen wird [7,9,15,27,33,34]. In der vorliegenden Studie unterschied sich aber die durchschnittliche GA und Standardabweichung von 4,53 % ± 16,72 % in Gruppe 1-3 sowie in Gruppe 4 mit −1,56 % ± 17,89 % kaum.…”
Section: Vorkommen Von Pathologischen V-kit-parameternunclassified
See 1 more Smart Citation
“…Los resultados obtenidos en nuestro estudio en niños son similares a los obtenidos en la población en general. Los estudios previos se consideran valores de normalidad las ganancias de 0,87 con una desviación standard de 0,10 y estableciendo unos valores patológicos menores de 0,8 [7,8]. En estudios que han investigado también solo la ganancia del canal horizontal mediante vHIT en niños con implante coclear han demostrado que es similar a los niños con audición normal [9] La disfunción vestibular y el deterioro del equilibrio resultante se han identificado como factores de riesgo importantes para el fracaso del implante coclear en los niños por qué es un factor que puede Ediciones Universidad de Salamanca / [ 24 ] Rev.…”
Section: Discussionunclassified